Risk assessment : a practical guide to assessing operational risks - Georgi Popov (John Wiley & Sons, 2024)
Covers the fundamentals of risk assessment and emphasizes taking a practical approach in the application of the techniques -Written as a primer for students and employed safety professionals covering the fundamentals of risk assessment and emphasizing a practical approach in the application of the techniques -Each chapter is developed as a stand-alone essay, making it easier to cover a subject -Includes interactive exercises, links, videos, and downloadable risk assessment tools -Addresses criteria prescribed by the Accreditation Board for Engineering and Technology (ABET) for safety programs